Knowledge Flow and Collaboration Under the World Bank’s New Operating Model : An Independent Evaluation - Independent Evaluation Group (World Bank, Washington, DC, 2019)
This evaluation reviews how well the World Bank's operating model has enabled knowledge flow and enhanced collaboration to deliver integrated solutions. The evaluation also looks at the incentives and behaviors the model inculcates. Evidence comes from both sides of the matrix.The evaluation finds that certain aspects of the operating model have shown value, especially its enabling of global knowledge flow. This is the effect of setting up GPs that operate more globally than before and GTs that provide useful strategic directions and coherence to cross-cutting priorities. The World Bank is able to provide integrated solutions addressing clients' important development problems because of the leadership of Country Directors supported by Program Leaders.However, evidence from the early years of implementing the model indicates that its structure and processes tend to inhibit collaboration and cause inefficiency, fragmentation, and internal competition. The interface between GPs and Regions has weakened. Some GPs lack coherent and systematic approaches to managing and investing in knowledge. There are concerns with insufficient contestability in the quality assurance process for operations and ASA products. If left unaddressed, these issues pose risks to the World Bank's ability to deliver for clients.IEG acknowledges management's proactive course correction of the operating model. The evaluation finds that this could be enhanced by continuously collecting and reviewing data on organizational effectiveness.These findings have led to six recommendations: (1) Strengthen the approach to knowledge in the GPs and GTs with clear goals, roles, and mechanisms, budgets commensurate with mandates, and metrics for knowledge uptake, quality, and influence; (2) improve budgeting systems to better incentivize knowledge flow and collaboration; (3) better link the GPs and Regions to improve coordination and enhance responsiveness to clients; ( 4) ensure a stronger and more consistent use and role of the Program Leaders as a mechanism for cross-sectoral collaboration, integrated solutions, and complex client dialogue; (5) review the existing quality assurance arrangements to improve the quality of knowledge embedded in advisory and financing services; and (6) ensure there is ongoing monitoring of the operating model and more continuity in change management efforts to enhance the organization's ability to attain its knowledge flow and collaboration goals.